Pengaruh Aktivitas Rasio, Ukuran Perusahaan, Struktur Modal, Likuiditas Dan Debt Ratio Terhadap Profitabilitas Sub Sektor Makanan Dan Minuman Di Bei 2009-2016 - Ariokunto Pangestu (Universitas Tarumanagara, 2019)
The purpose of this research is to determine the effect of the ratio of activity, firm size, capital structure, liquidity and debt ratio to company’s profitability in manufacturing companies food sub-sector and bevarages listed in Indonesia Stock Exchange. The sampling method is done by using purposive sampling. The method of collecting secondary data is taken from the IDX that publishes the financial statements. This research uses several analytical methods, descriptive statistical analysis, classical assumption test, multiple regression analysis, simultaneous test (F test), partial test (T test) and determnasi test (adjusted R2) to test its hypothesis using Eviews 9. The results showed that total asset turnover of debt equity ratio has a positive significance, size has positive not significant, current ratio has negative ratio is not significant and debt has significant negative effect to profitability of company which measured by using Return Of Equity. F-test results show that all independent variables in this research simultaneously have a significant effect on the return of equity of companies in the food and beverages sub-sector listed on the Indonesia Stock Exchange. In the Adjusted R2 test, the analysis results show that 95.2% return of equity is influenced by the independent variables of this research while the remaining 4.8% is influenced by other factors not studied.